ANALISIS KONDISI PSIKOLOGIS SISWA SERTA IMPLIKASINYA TERHADAP PROGRAM BIMBINGAN DAN KONSELING - Stevani, Hayu; Riska Andriani; Fijriani, Fijriani (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2019)
Psychological conditions are things that can not be seen directly by the five senses. For example sleeplessness, there are feelings of guilt, thinking no life-threatening, it can not respond to others when asked, and many other psychological problems. In guidance and counseling, AUM umum helps to unravel the psychological conditions through nine field problems. The population and sample of the study included 91 students of class VII and VIII SMP IT Tariq ibn Ziyad Boarding School using AUM umum F-3 for data collection. Results of research for class VII revealed the problem area in PDP,  HSO,and JDK, and for class VIII is the problem area in PDP,and HSO got the highest yield of nine-field problems. Based on the interpretation of general AUM results, a description of the student's psychological condition can be an input for the school counselor to create the program and perform the service, most specifically to the field of issue that gets special attention.